PENGARUH GROWTH OPPORTUNITY, NET WORKING CAPITAL, FIRM SIZE, PROFITABILITAS DAN CASH FLOW TERHADAP CASH HOLDING PERUSAHAAN NON CONSUMER CYCLICAL YANG TERDAFTAR DI BEI - Wijayanti, Esa; Cahyo, Heru; Wahyuni, Endang Sri (JURNAL LENTERA AKUNTANSI, 2023)
This study aims to analyze the effect of growth opportunity, net working capital, firm size, profitability, and cash flow on cash holding in non-cyclical consumer companies listed on the Indonesia Stock Exchange during the period 2018 to 2021. This research is a quantitative study with the sampling technique is purposive sampling technique and the research method used is panel data regression analysis. The results of data analysis show that growth opportunity, net working capital has a positive and insignificant effect on cash holding while firm size, and profitability have a negative and insignificant effect on cash holding. Meanwhile, cash flow has a significant positive effect on cash holding, in this case strong cash flow indicates that the company is able to generate consistent income from its operational activities. With sufficient cash flow, companies can maintain a level of cash reserves to maintain liquidity in emergency or uncertain situations. If cash inflows are greater than cash outflows, then the company will have a surplus of cash funds that can be held in reserve or used for other purposes. Therefore, the company must pay close attention to the cash inflow and outflow cycle. This research provides important insights for company management in making decisions regarding cash allocation and risk management strategies. Keyword: Growth Opportunity, Net Working Capital, Firm Size, Profitabilitas, Cash Flow, Cash Holding